Corrosion-resistant titanium alloy bar and method for manufacturing the same

CN122918385APending Publication Date: 2026-10-16CHANGSHA HAIYI LAKE HYDROGEN ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510842219.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,这些合金元素的添加往往伴随着生产成本的增加,并且对钛合金的力学性能和加工工艺提出更高要求

Benefits of technology

1.通过添加钌(Ru)元素,改善了钛合金的耐蚀性和导电性,使用该钛合金制备的工件使用寿命显著延长。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918385A_ABST
    Figure CN122918385A_ABST
Patent Text Reader

Abstract

The application relates to the field of titanium alloy, and discloses a kind of corrosion-resistant titanium alloy bar and its preparation method, aiming at the problem that titanium alloy is prone to pitting corrosion, crevice corrosion in chlorine ion-containing environment such as seawater, physiological environment, leading to performance decline, by optimizing alloy composition design and preparation process, the corrosion resistance is significantly improved. Specifically, corrosion-resistant alloy elements such as palladium and molybdenum are added, and microstructure control technology is combined, while maintaining the excellent mechanical properties of titanium alloy, effectively improving its resistance to localized corrosion in 3.5% NaCl solution and other corrosion media, prolonging the service life of the material. The method overcomes the defect that the traditional surface treatment coating is easy to fail, reduces the harsh requirements of alloy element addition on processing technology, and provides a high-performance, long-life corrosion-resistant titanium alloy material solution for marine engineering, biomedical and other fields. The application has the advantages of improving the corrosion resistance of titanium alloy in chlorine-containing environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of titanium alloys, and specifically relates to a method for preparing a corrosion-resistant titanium alloy bar. Background Technology

[0002] Titanium alloys are widely used in aerospace, chemical, marine engineering, and biomedical fields due to their excellent mechanical properties and corrosion resistance. However, in environments containing chloride ions, such as the ocean and human physiological environments, the corrosion resistance of conventional titanium alloys still has certain limitations. Especially in environments simulating seawater with 3.5% NaCl solution, the surface of titanium alloys is susceptible to localized corrosion such as pitting and crevice corrosion, leading to a decline in material properties and severely affecting their service life.

[0003] Currently, several methods are commonly used to improve the corrosion resistance of titanium alloys: adding corrosion-resistant alloying elements, surface treatment, and altering the microstructure. Adding alloying elements such as palladium, molybdenum, vanadium, and chromium can improve the corrosion resistance of titanium alloys to some extent. However, the addition of these alloying elements often increases production costs and places higher demands on the mechanical properties and processing technology of the titanium alloys. Surface treatment technologies such as anodizing, electroplating, and laser surface modification can effectively improve the corrosion resistance of titanium alloys, but in practical applications, the surface coating may fail due to wear and peeling, leading to a decrease in the material's corrosion resistance.

[0004] Against this backdrop, developing a titanium alloy that maintains excellent corrosion resistance in corrosive environments by adjusting alloy composition and optimizing preparation processes has become a research hotspot in the field of titanium alloy materials. This patent proposes a novel method for preparing corrosion-resistant titanium alloys. By optimizing alloy composition design and preparation processes, the corrosion resistance of titanium alloys in chlorine-containing environments is improved, thereby meeting the needs of marine engineering, biomedical fields, and other areas for corrosion-resistant materials. Summary of the Invention

[0005] (a) Technical problems to be solved In view of the defects and deficiencies of the existing technology, firstly, the present invention provides a corrosion-resistant titanium alloy; secondly, the present invention provides a method for preparing a corrosion-resistant titanium alloy, which has the advantages of improving the corrosion resistance of titanium alloy in chlorine-containing environments, and solves the problems in the background technology mentioned above.

[0006] (II) Technical Solution To achieve the aforementioned goal of improving the corrosion resistance of titanium alloys in chlorine-containing environments, the present invention provides the following technical solution: In a first aspect, the present invention provides a corrosion-resistant titanium alloy comprising elements such as aluminum, molybdenum, tungsten, and the noble metal ruthenium; the corrosion-resistant titanium alloy rod, by mass content, contains Al 5.6-6.0, Ru 0.15-0.25, Mo 0.8-1.2, Zr 1.5-2.0, O≤0.12, N≤0.05, with the balance being Ti and unavoidable impurities; it has an equiaxed α-grain structure of 8-15 μm, continuous Ti, Ru, and Mo distribution at grain boundaries, an O2 nanofilm of 2-5 nm, and an Al3Zr precipitate phase less than 200 nm within the grains.

[0007] Secondly, the present invention provides a method for preparing a corrosion-resistant titanium alloy, comprising the following steps: Step 1: Melt the alloy raw materials to obtain a cast alloy billet; Step 2: The as-cast alloy is subjected to high-temperature billet treatment, followed by hot forging treatment to obtain titanium alloy bars. Step 3: Heat treat the densified alloy rod to obtain the finished corrosion-resistant titanium alloy rod.

[0008] Raw material smelting and ingot preparation: The raw materials containing titanium, aluminum, molybdenum, zirconium and ruthenium are accurately weighed and mixed evenly in proportion, and pressed into electrode blocks with a certain density; multiple electrode blocks are welded into consumable electrodes; in a vacuum environment, the consumable electrodes are smelted multiple times using a consumable electrode arc melting furnace to obtain titanium alloy ingots with uniform composition.

[0009] High-temperature forging: The titanium alloy ingot obtained in step one is heated to the temperature of the single-phase region of titanium alloy for homogenization and heat preservation treatment; after the heat preservation is completed, the ingot is repeatedly upset and drawn by forging equipment at high temperature, and the deformation amount and the final temperature of forging are controlled in each heat.

[0010] Two-phase forging: The alloy after the blanking forging in step two is heated to the temperature of the two-phase region where the α phase and β phase of titanium alloy coexist and held at that temperature. After the holding period, the forging equipment is used again to perform repeated upsetting and drawing forging operations at the temperature of the two-phase region. The deformation amount of each forging, the cumulative total deformation amount and the final forging temperature are controlled to finally forge the bar stock of the required specifications.

[0011] Solution aging heat treatment: The titanium alloy bar obtained by forging in step three is heated to the solution temperature and held at that temperature. After holding, the bar is cooled to room temperature by rapid cooling. Then, the bar is heated to the aging temperature and held at that temperature. After holding, the bar is cooled to room temperature by air cooling. Finally, a corrosion-resistant titanium alloy bar product with the microstructure characteristics described in claim 1 is obtained.

[0012] Preferred, refined control of the smelting process: When using a vacuum consumable electrode arc melting furnace, the melting process needs to be repeated 3-4 times to ensure the uniformity of the alloy composition. If the number of melting times is insufficient, element segregation is likely to occur, reducing the corrosion resistance. The density of the electrode block is strictly controlled within the range of 3.4-3.65 g / cm³; if the density is too low, impurities are more likely to fall off during smelting, increasing the risk of inclusions and damaging the uniformity of the structure. The melting temperature is limited to 1900-1920℃; deviation from the temperature will cause elements such as ruthenium and molybdenum to volatilize or oxidize, weakening the ability to form grain boundary nanofilms.

[0013] Preferred microstructure control in single-phase forging: The ingot is heated to the single-phase region of 1130-1180℃ for homogenization treatment; if the temperature is below 1130℃, the primary α phase cannot be completely dissolved, leading to the risk of forging cracks; if the temperature is above 1180℃, the grains grow abnormally, weakening the strength. The forging ratio per heat should not be less than 2, and the total forging ratio is achieved through 1-3 heats. Insufficient forging ratio will lead to insufficient crushing of the original β grains. When the final forging temperature is below 940℃, the deformation resistance will surge and microcracks will easily form. The initial forging temperature should be ≥1050℃ to ensure that the material is in the single-phase region; if the temperature is too low, some α phase residue will hinder dynamic recrystallization and make it impossible to obtain equiaxed primary α phase.

[0014] Preferably, the phase ratio is controlled during two-phase forging: The forging billet is heated to 980℃ in the α+β two-phase region for secondary forging. Temperature deviation will change the α / β phase ratio. If it is below 980℃, the thickness of the secondary α phase lath increases and the creep performance is reduced. If it is above 980℃, the proportion of equiaxed α phase decreases and the thermal stability is affected. The forging ratio per firing is ≥2.6, and the total forging ratio is ≥8. Insufficient forging ratio will lead to uneven distribution of secondary α phase. When the final forging temperature is below 850℃, the β phase transformation is incomplete, and the residual stress increases. During the elongation process, the height-to-diameter ratio should be controlled at 2:1, and the upsetting deformation should be ≥50%. Imbalance in shape proportions or insufficient deformation will lead to uneven texture and weaken isotropic properties.

[0015] Preferably, the aging response of solution treatment is optimized: Repeated upsetting and drawing deformation can more effectively break up coarse as-cast structures, promote dynamic recrystallization, and achieve full grain refinement and homogenization. The solution treatment temperature should be 1020℃ or 990℃, and the heating rate should be 6-15℃ / min. Temperatures that are too high, above 1020℃, will cause the oxide film at the grain boundaries to crack, and heating rates that are too fast, above 15℃ / min, will cause thermal stress cracking. The holding time should be 150-360 min; if the time is less than 150 min, the solute elements will not diffuse sufficiently, and if the time is too long, the grains will coarsen and the elongation will be reduced. After solution treatment, rapid cooling with oil is used; if air cooling or water cooling is used, mismatched cooling rates will result in residual non-equilibrium structures, affecting the aging response.

[0016] Preferred method for controlling the precipitated phase during aging treatment: The aging temperature is 650-750℃, and the holding time is 6-8 hours. When the temperature is below 650℃, the nucleation driving force of the precipitated phase is insufficient, and when the temperature is above 750℃, the precipitated phase coarsens, both of which will reduce the strengthening effect. The heat preservation time should be strictly controlled within 6-8 hours; less than 6 hours will result in insufficient density of the precipitated phase, while more than 8 hours will cause over-aging and strength reduction. After aging, air cooling to room temperature should be used; if forced air cooling or water cooling is used, the cooling rate will be too fast, which will lead to residual stress concentration and increase the tendency to crack.

[0017] Preferred post-forging treatment and raw material control: After forging, the bar stock is rolled into a round shape; if this process is omitted, residual surface defects will become corrosion initiation points, shortening the service life. The final forging temperature is controlled at ≥850℃ throughout the process; a lower temperature leads to an imbalance in the retention ratio of the β phase, which destroys the synergistic strengthening effect between the equiaxed α phase and the lath α phase. The raw material is 0A grade sponge titanium with a particle size of 3-12.7mm. If the particle size is too large (greater than 12.7mm), it will introduce shrinkage cavities; if it is too small (less than 3mm), it will be easily oxidized, both of which will deteriorate the corrosion resistance.

[0018] (III) Beneficial Effects Compared with the prior art, the present invention provides a corrosion-resistant titanium alloy rod and its preparation method, which has the following beneficial effects: 1. By adding ruthenium (Ru), the corrosion resistance and electrical conductivity of titanium alloys are improved, and the service life of workpieces made using this titanium alloy is significantly extended.

[0019] 2. The raw materials used in this invention, excluding sponge titanium, are mainly intermediate alloys, thus achieving the goal of controlling the content of impurity elements in the alloy. This also reduces the risk of element segregation and inclusions.

[0020] 3. This invention involves heat-treating the alloy billet before deformation, which on the one hand yields a denser alloy billet; on the other hand, it allows the titanium alloy ingot to maintain a high temperature during deformation, achieving hot deformation. Furthermore, the hot rolling deformation method employed in this invention facilitates grain breakage, refining and deforming the original β grains, eliminating structural defects, and improving alloy strength. 4. This invention proposes a method for preparing titanium alloy bars with an equiaxed microstructure. This microstructure exhibits excellent strength at both room temperature and high temperature, strong thermal stability and creep resistance, and strong corrosion resistance. The room temperature tensile strength is greater than 1000 MPa, and the elongation is greater than 12%. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the structure of the present invention.

[0022] Figure 2 This is a schematic diagram of the method of the present invention.

[0023] Figure 3 The metallographic image shows the differences in size and distribution of the equiaxed α phase.

[0024] Figure 4 The metallographic image shows the differences in size and distribution of the equiaxed α phase.

[0025] Figure 5 The metallographic image shows the differences in size and distribution of the equiaxed α phase.

[0026] Figure 6 The metallographic image shows the differences in size and distribution of the equiaxed α phase.

[0027] Figure 7 The metallographic image shows the differences in size and distribution of the equiaxed α phase.

[0028] Figure 8 The metallographic image shows the differences in size and distribution of the equiaxed α phase.

[0029] Figure 9 The high-resolution TEM image reveals the mechanism of Ru atom segregation at grain boundaries.

[0030] Figure 10 The electrochemical polarization curves quantify the difference in corrosion resistance between Example 2 and CP-Ti. Detailed Implementation

[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] Example 1 Please see Figure 1 As shown in the embodiment of the present invention, a method for preparing a corrosion-resistant titanium alloy rod includes: Raw material smelting and ingot preparation: The raw materials containing titanium, aluminum, molybdenum, zirconium and ruthenium are accurately weighed and mixed evenly in proportion, and pressed into electrode blocks with a certain density; multiple electrode blocks are welded into consumable electrodes; in a vacuum environment, the consumable electrodes are smelted multiple times using a consumable electrode arc melting furnace to obtain titanium alloy ingots with uniform composition.

[0033] The application of refined control in smelting processes is as follows: A vacuum consumable electrode arc melting furnace is used, where electrode rods are repeatedly melted 3-4 times in a vacuum environment. This equipment can achieve a high-purity melting environment, avoiding the introduction of external impurities. The number of repeated meltings must be strictly controlled to 3-4 times: Insufficient number (<3 times): Uneven distribution of alloying elements, prone to local segregation, leading to decreased corrosion resistance; Excessive number (>4 times): Increased energy consumption and limited improvement in compositional uniformity, reducing economic efficiency; Electrode block density control: The electrode block density must be controlled within the range of 3.4-3.65 g / cm³, achieved through a pressing process: Too low a density (<3.4 g / cm³): Impurities (such as oxides and inclusions) easily detach from the electrode blocks during the melting process, contaminating the alloy and disrupting the uniformity of the microstructure. High density (>3.65g / cm³): Increases pressing difficulty and cost, but does not improve smelting quality; Smelting temperature limit: Smelting temperature is strictly limited to 1900-1920℃, controlled by equipment power and thermocouple feedback; Low temperature (<1900℃): High melting point elements such as ruthenium and molybdenum do not melt sufficiently, easily forming unmelted inclusions and weakening the ability to form grain boundary nanofilms; High temperature (>1920℃): Increased volatilization of titanium and alloy elements, leading to compositional shift, while increasing the risk of oxidation and deteriorating corrosion resistance.

[0034] By adding ruthenium (Ru), the corrosion resistance and electrical conductivity of titanium alloys are improved, and the service life of workpieces made using this titanium alloy is significantly extended.

[0035] The microstructure control of single-phase forging is as follows: The ingot needs to be heated to 1130-1180℃ (single-phase region) for homogenization, with precise temperature control achieved through a resistance furnace: Too low a temperature (<1130℃): the primary α phase inside the material is not completely dissolved, leading to localized stress concentration during forging and increasing the risk of cracking; Too high a temperature (>1180℃): grains grow rapidly due to overheating, resulting in decreased strength and reduced thermal stability of the finished product; Forging deformation control: each forging pass must achieve a deformation amount of not less than 2 times (forging ratio), accumulating the total deformation amount through 1-3 forging passes; insufficient forging ratio (< 2) The original β grains are not sufficiently broken, resulting in poor uniformity of the microstructure. If the final forging temperature is below 940℃, the material's deformation resistance will increase sharply, making it prone to microcracks. Cumulative total forging ratio: Grain refinement is achieved through multiple forging processes to avoid excessive deformation in a single forging, which could lead to cracking. Initial forging temperature guarantee: The initial forging temperature must be ≥1050℃ and monitored in real time by an infrared thermometer. If the temperature is too low (<1050℃): Some α phase remains inside the material, hindering the dynamic recrystallization process and preventing the formation of a uniform equiaxed primary α phase microstructure, resulting in substandard mechanical properties.

[0036] The raw materials used in this invention, excluding sponge titanium, are mainly intermediate alloys, thereby controlling the content of impurity elements in the alloy. This also reduces the risk of element segregation and inclusions.

[0037] High-temperature forging: The titanium alloy ingot obtained in step one is heated to the temperature of the single-phase region of titanium alloy for homogenization and heat preservation treatment; after the heat preservation is completed, the ingot is repeatedly upset and drawn by forging equipment at high temperature, and the deformation amount and the final temperature of forging are controlled in each heat.

[0038] The phase ratio control for two-phase region forging is as follows: Heating temperature control: The forging billet needs to be heated to the α+β two-phase region (about 980℃) for secondary forging. Precise temperature control is achieved through a resistance furnace: If the temperature is too low (<980℃): the proportion of α phase inside the material is too high, and the secondary α phase laths thicken after forging, resulting in a decrease in high-temperature creep performance; If the temperature is too high (>980℃): the proportion of β phase increases, and the content of equiaxed α phase decreases after forging, affecting the dimensional stability of the material under high-temperature conditions; Forging deformation control: Each forging pass must achieve a deformation of not less than 2.6 times (forging ratio), and the total deformation is accumulated through 2-3 forging passes (total forging ratio ≥ 8): Insufficient forging ratio (< 2.6 / pass): The secondary α phase is unevenly distributed. If the final forging temperature is below 850℃, the transformation process from β phase to α phase is hindered, and the residual internal stress increases; Accumulated total forging ratio: The microstructure is gradually optimized through multiple forging passes to avoid the risk of cracking due to excessive deformation in a single pass; Coordinated control of shape and deformation: The height-to-diameter ratio must be controlled at 2:1 during the drawing process, and the upsetting deformation must reach more than 50%; Imbalanced shape ratio: If the height-to-diameter ratio deviates from 2:1, the metal flow is uneven during forging, which easily leads to texture agglomeration and material anisotropy; Insufficient deformation (< 50%): The grains are not fully broken, the dynamic recrystallization process is hindered, and the comprehensive mechanical properties of the material are weakened.

[0039] Two-phase forging: The alloy after the blanking forging in step two is heated to the temperature of the two-phase region where the α phase and β phase of titanium alloy coexist and held at that temperature. After the holding period, the forging equipment is used again to perform repeated upsetting and drawing forging operations at the temperature of the two-phase region. The deformation amount of each forging, the cumulative total deformation amount and the final forging temperature are controlled to finally forge the bar stock of the required specifications.

[0040] Post-forging processing and raw material control are as follows: Post-forging surface treatment: After forging, the bar stock needs to be rounded to remove the surface oxide layer and microcracks through machining. Necessity of the process: If the rounding process is omitted, the surface defects generated by forging (such as folds and pits) will become channels for the penetration of corrosive media, significantly reducing the corrosion resistance life of the material in a chloride ion environment. Final forging temperature control: The final forging temperature must be ensured to be no less than 850℃ throughout the forging process, and monitored in real time by an infrared thermometer. If the temperature is too low (<850℃): the transformation process from β phase to α phase is hindered, resulting in an imbalance in the ratio of equiaxed α phase to lath α phase, weakening the synergistic strengthening effect of the two, and reducing the fatigue resistance of the material. Raw material particle size screening: 0A grade sponge titanium (3-12.7mm) with a specific particle size range is selected as the matrix raw material. If the particle size is too large (>12.7mm): it is difficult for gas to escape during melting, and micro-shrinkage porosity is easily formed. If the particle size is too small (<3mm): the specific surface area increases, the tendency for oxidation adsorption increases, and the alloy composition segregates, both of which will deteriorate the corrosion resistance of the material.

[0041] This invention involves heat-treating the alloy billet before deformation, which on the one hand yields a denser alloy billet; on the other hand, it allows the titanium alloy ingot to maintain a high temperature during deformation, achieving hot deformation. Furthermore, the hot rolling deformation method employed in this invention facilitates grain breakage, refining and deforming the original β grains, eliminating structural defects, and improving alloy strength. Solution aging heat treatment: The titanium alloy bar obtained by forging in step three is heated to the solution temperature and held at that temperature. After holding, the bar is cooled to room temperature by rapid cooling. Then, the bar is heated to the aging temperature and held at that temperature. After holding, the bar is cooled to room temperature by air cooling. Finally, a corrosion-resistant titanium alloy bar product with the microstructure characteristics described in claim 1 is obtained.

[0042] The aging response of solution treatment is optimized as follows: The deformation process plays a crucial role in microstructure optimization. By repeatedly alternating upsetting and drawing operations, coarse grains in the as-cast microstructure can be effectively broken up, promoting dynamic recrystallization and achieving sufficient grain refinement and homogenization, thus laying the microstructure foundation for subsequent solution treatment. Controlling the solution temperature and heating rate is essential. Solution treatment must be carried out within a specific temperature range (approximately 990-1020℃), and uniform heating must be achieved by controlling the heating rate (6-15℃ / min). Excessive temperature (>1020℃) can cause the oxide film at grain boundaries to crack due to overheating, reducing the material's corrosion resistance. Excessive heating (>15℃ / min) can lead to a sudden increase in internal thermal stress, increasing the risk of cracking. Optimizing the holding time is also crucial. Solution treatment needs to be held for a sufficient time (150-360 minutes) to ensure sufficient diffusion of solute elements. Insufficient time (<150 minutes) results in inadequate diffusion of solute elements, leading to component segregation. Excessive time (>360 minutes) causes grain coarsening due to prolonged high temperatures, reducing the material's elongation. Cooling method selection: After solution treatment, oil cooling is required to achieve rapid cooling; air cooling or water cooling: the cooling rate is not matched with the phase transformation characteristics of the material, and non-equilibrium structures are easily left behind, affecting the effect of subsequent aging treatment.

[0043] The precipitation phase control during aging treatment is as follows: Aging temperature and precipitate control: Aging treatment must be carried out within a specific temperature range (approximately 650-750℃). Precise control of the precipitate is achieved by controlling the holding time (6-8 hours): Too low a temperature (<650℃): Insufficient nucleation driving force for the precipitate results in insufficient strengthening phase quantity and limited improvement in material strength; Too high a temperature (>750℃): The precipitate coarsens rapidly due to overheating, reducing the interfacial bonding strength with the matrix and weakening the strengthening effect; Optimization of holding time: Aging treatment must be maintained for a sufficient time to ensure sufficient precipitate formation: Insufficient time (<6 hours): Insufficient precipitate density, failing to form an effective strengthening effect; Too long a time (>8 hours): Excessive coarsening of the precipitate, the material enters an over-aged state, and the strength significantly decreases; Cooling method selection: After aging treatment, slow cooling to room temperature using air cooling is required: Forced air cooling or water cooling: Excessive cooling rate leads to concentration of residual stress inside the material, increasing the risk of cracking during subsequent processing or use.

[0044] This invention proposes a method for preparing titanium alloy bars with an equiaxed microstructure. This microstructure exhibits excellent strength at both room temperature and high temperature, strong thermal stability and creep resistance, and strong corrosion resistance. The room temperature tensile strength is greater than 1000 MPa, and the elongation is greater than 12%.

[0045] Example 2 Preparation and phase structure control verification of corrosion-resistant titanium alloy bars: Purpose of the example: Verify the key roles of hot forging temperature, forging ratio, and heating temperature in the formation of equiaxed primary α phase and lath secondary α phase, and clarify the influence of process parameter deviations on microstructure.

[0046] Implementation steps: 1. Titanium alloy ingredients The raw materials are precisely weighed according to the following mass percentages: Al 5.8%, Ru 0.2%, Mo 1.0%, Zr 1.8%, O 0.1%, N 0.03%, with the balance being Ti and unavoidable impurities. The raw materials are mixed evenly, with Ti selected from 0A grade sponge titanium (6mm particle size), Al added in the form of Al-50Ti master alloy and aluminum granules, and other elements using low-impurity master alloys.

[0047] 2. Preparation of titanium alloy ingots The mixture was pressed into electrode blocks (density 3.5 g / cm³), stacked and welded into consumable electrodes, and repeatedly melted 4 times in a vacuum consumable electrode arc melting furnace at a melting temperature of 1910℃ to obtain φ690×1320mm ingots, which were then removed from the risers and kept for later use.

[0048] 3. Titanium alloy ingot blanking (single-phase zone forging) Heat treatment: The ingot is heated to 1150℃ (single-phase zone) in a resistance furnace and held for 2 hours to ensure temperature uniformity.

[0049] Hot forging operation: Forging step 1: Upsetting to φ590mm (deformation 55%), drawing to φ620×L mm, height-to-diameter ratio 2.5:1, forging ratio 2.5, final forging temperature 950℃; Forging cycles 2-3: Repeat the upsetting-drawing process, with a forging ratio of 2.5 per cycle, a total forging ratio of 7.5, and a final forging temperature of 940℃.

[0050] Key controls: If the heating temperature is below 1130℃, the microstructure shows that the primary α phase is not completely dissolved, making it prone to cracking during forging; if the final forging temperature is below 940℃, the deformation resistance increases sharply, leading to the formation of microcracks.

[0051] 4. Preparation of titanium alloy bars (two-phase region forging) Heat treatment: After the billet is opened, heat the forging billet to 990℃ (α+β two-phase region) and hold for 2 hours.

[0052] Hot forging operation: Forging cycles 1-3: Upsetting to octagonal 675×1250mm, drawing to φ450mm, holding in the furnace for 150min, and then drawing to φ350×3500mm. The forging ratio per cycle is 2.8, the total forging ratio is 6.0, and the final forging temperature is 860℃.

[0053] Key controls: When the heating temperature is below 980℃, the thickness of the secondary α phase lath increases and the creep performance decreases; when the temperature is above 1000℃, the proportion of equiaxed α phase decreases and the thermal stability decreases.

[0054] If the total forging ratio is less than 6.0, the secondary α phase is unevenly distributed. When the final forging temperature is less than 850℃, the β phase transformation is incomplete, and the residual stress increases.

[0055] 5. Heat treatment of titanium alloy bars Solution treatment: Under argon protection, the temperature is increased to 1000℃ at a rate of 10℃ / min, held for 240min, and then cooled to room temperature with oil.

[0056] Aging treatment: After holding at 700℃ for 7 hours, air cool to room temperature.

[0057] Key controls: When the solution temperature is above 1020℃, the oxide film at the grain boundaries ruptures; when it is below 990℃, the diffusion of solute elements is insufficient.

[0058] Implementation Result Analysis 1. Phase structure formation mechanism Equiaxed primary α phase: Dynamic recrystallization is achieved through high-temperature forging in the single-phase region (1130-1180℃). Upsetting deformation of ≥55% can fully break up the as-cast structure and form equiaxed grains. If the temperature deviates from this range or the forging ratio is insufficient, the proportion of primary α phase decreases and the uniformity of the structure decreases.

[0059] Lath-shaped secondary α phase: During forging in the α+β two-phase region (980-1000℃), the retention ratio of the β phase and the amount of deformation work together to form a lath-shaped secondary α phase. If the heating temperature is below 980℃, the thickness of the secondary α phase increases; above 1000℃, the proportion of equiaxed α phase decreases.

[0060] 2. Impact of deviations in process parameters: Temperature deviation: When the temperature in the single-phase region is below 1130℃, the primary α phase remains, causing forging cracks; when the temperature in the two-phase region is below 980℃, the secondary α phase coarsens, and when it is above 1000℃, the equiaxed α phase decreases. Insufficient forging ratio: When the total forging ratio is less than 6.0, the secondary α phase is unevenly distributed, and the β phase transformation is incomplete when the final forging temperature is less than 850℃; Holding time: A holding time of 150-360 minutes for solution treatment can ensure sufficient diffusion of solute elements. Insufficient time will result in insufficient diffusion, while excessive time will cause grain coarsening.

[0061] Example Conclusion: This embodiment successfully prepared corrosion-resistant titanium alloy bars possessing both equiaxed primary α phase and lath secondary α phase by precisely controlling the hot forging temperature, forging ratio, and heating temperature. Deviations in process parameters directly lead to phase structure imbalance, manifested as decreased corrosion resistance or deterioration of mechanical properties, verifying the strong correlation between process parameters and microstructure properties in the claims.

[0062] Example 3 Step 1: Add small-particle 0a grade sponge titanium and aluminum in the form of intermediate alloy and aluminum granules. Add the remaining elements in the form of intermediate alloy. After weighing the ingredients according to the formula of 5.8 wt.% aluminum, 1 wt.% molybdenum, 2 wt.% Zr, 0.15 wt.% ruthenium, and the balance is titanium, mix them evenly to obtain mixed metal powder.

[0063] Step 2: Press the above uniformly mixed ingredients into electrodes using a hydraulic press. The density of the electrode blocks is 3.4~3.65 g / cm3. Stack and weld multiple electrode blocks into consumable electrodes. Repeatedly melt the alloy raw materials 4 times in a vacuum consumable electrode arc melting furnace at a temperature of

[1880] ~

[1900] ℃ to ensure the uniformity of the ingot composition. After the ingot melting is completed, the riser is removed. Step 3: Using a resistance furnace, heat the corrosion-resistant titanium alloy ingot to 1150℃ in the single-phase region for homogenization treatment. Then, use a high-speed forging machine or hydraulic press to repeatedly upset and draw the ingot three times, with a forging ratio of not less than 2.5 per forging. The initial forging temperature should be ≥1050℃, and the final forging temperature should be ≥940℃. Before forging, chamfer the edges at a speed of 40~60 mm / s (upsetting deformation should be 55%, and the drawing circumference should match the height-to-diameter ratio of 2:1). Upset the 690×1320 cm ingot to 590±10 cm, draw it to 620×L cm, and chamfer it to 675±10×1250 cm.

[0064] Step 4: Using a resistance furnace, heat the corrosion-resistant titanium alloy after billet preparation to the α+β two-phase region at 1000℃ and hold for 2 hours. Then, repeatedly upsetting and drawing the billet three times using a high-speed forging mill or hydraulic press. The forging ratio per forging pass should be no less than 2.8, the total forging ratio no less than 8, and the final forging temperature no less than 850℃. The drawing rate is 20~25mm / s. The billet can be reheated as needed for further drawing. For an octagonal billet of 675×1250cm, draw it to 450±10cm, reheat it in the furnace for 180 minutes, and then draw it to 350×3500cm.

[0065] Step 5: Heat treatment is performed on the hot-forged titanium alloy bar. The heat treatment method is solution treatment at a temperature of 980℃, a heating rate of 10℃ / min, and a holding time of 240min. After heat treatment, the bar is cooled to room temperature by oil cooling, and then artificially aged at 680℃ for 6 hours before being air-cooled to room temperature.

[0066] Example 4 Step 1: Add small-particle 0a grade sponge titanium and aluminum in the form of intermediate alloy and aluminum granules. Add the remaining elements in the form of intermediate alloy. After weighing the ingredients according to the formula of 5.8 wt.% aluminum, 1 wt.% molybdenum, 1 wt.% tungsten, 0.2 wt.% ruthenium, and the balance being titanium, mix them evenly to obtain mixed metal powder.

[0067] Step 2: Press the above uniformly mixed ingredients into electrodes using a hydraulic press. The density of the electrode blocks is 3.4~3.65 g / cm3. Stack and weld multiple electrode blocks into consumable electrodes. Repeatedly melt the alloy raw materials 4 times in a vacuum consumable electrode arc melting furnace at a temperature of

[1880] ~

[1900] ℃ to ensure the uniformity of the ingot composition. After the ingot melting is completed, the riser is removed. Step 3: Using a resistance furnace, heat the corrosion-resistant titanium alloy ingot to 1150℃ in the single-phase region for homogenization treatment. Then, use a high-speed forging machine or hydraulic press to repeatedly upset and draw the ingot three times, with a forging ratio of not less than 2.5 per forging. The initial forging temperature should be ≥1050℃, and the final forging temperature should be ≥940℃. Before forging, chamfer the edges at a speed of 40~60 mm / s (upsetting deformation should be 55%, and the drawing circumference should match the height-to-diameter ratio of 2:1). Upset the 690×1320 cm ingot to 590±10 cm, draw it to 620×L cm, and chamfer it to 675±10×1250 cm.

[0068] Step 4: Using a resistance furnace, heat the corrosion-resistant titanium alloy after billet preparation to the α+β two-phase region at a temperature of 1000℃. Then, repeatedly upsetting and drawing the billet three times using a high-speed forging mill or hydraulic press. The forging ratio per forging pass should be no less than 2.8, the total forging ratio no less than 8, and the final forging temperature no less than 850℃. The drawing rate is 20~25mm / s. The billet can be reheated as needed for further drawing. For an octagonal billet of 675×1250cm, draw it to 450±10cm, reheat it in the furnace for 180min, and then draw it to 350×3500cm.

[0069] Step 5: The hot-forged titanium alloy bar is subjected to heat treatment, specifically solution treatment at 980℃, with a heating rate of 10℃ / min and a holding time of 240min. After heat treatment, it is oil-cooled to room temperature, then artificially aged at 680℃ for 6 hours and air-cooled to room temperature. Example 5 Step 1: Add small-particle 0a grade sponge titanium and aluminum in the form of intermediate alloy and aluminum granules. Add the remaining elements in the form of intermediate alloy. After weighing the ingredients according to the formula of 5.8 wt.% aluminum, 1 wt.% molybdenum, 1 wt.% tungsten, 0.25 wt.% ruthenium, and the balance being titanium, mix them evenly to obtain mixed metal powder.

[0070] Step 2: Press the above uniformly mixed ingredients into electrodes using a hydraulic press. The density of the electrode blocks is 3.4~3.65 g / cm3. Stack and weld multiple electrode blocks into consumable electrodes. Repeatedly melt the alloy raw materials 4 times in a vacuum consumable electrode arc melting furnace at a temperature of

[1880] ~

[1900] ℃ to ensure the uniformity of the ingot composition. After the ingot melting is completed, the riser is removed. Step 3: Using a resistance furnace, heat the corrosion-resistant titanium alloy ingot to 1150℃ in the single-phase region for homogenization treatment. Then, use a high-speed forging machine or hydraulic press to repeatedly upset and draw the ingot three times, with a forging ratio of not less than 2.5 per forging. The initial forging temperature should be ≥1050℃, and the final forging temperature should be ≥940℃. Before forging, chamfer the edges at a speed of 40~60 mm / s (upsetting deformation should be 50%, and the drawing circumference should match the height-to-diameter ratio of 2.5:1). Upset the 690×1320 cm ingot to 590±10 cm, draw it to 620×L cm, and chamfer it to 675±10×1250 cm.

[0071] Step 4: Using a resistance furnace, heat the corrosion-resistant titanium alloy after billet preparation to the α+β two-phase region at a temperature of 1000℃. Then, repeatedly upsetting and drawing the billet three times using a high-speed forging mill or hydraulic press. The forging ratio per forging pass should be no less than 2.8, the total forging ratio no less than 6, and the final forging temperature no less than 850℃. The drawing rate is 20~25mm / s. The billet can be reheated as needed and drawn again. For an octagonal billet of 675×1250cm, draw it to 450±10cm, reheat it in the furnace for 150min, and then draw it to 350×3500cm.

[0072] Step 5: Heat treatment is performed on the hot-forged titanium alloy bar. The heat treatment method is solution treatment, the temperature is 1020℃, the heating rate is 10℃ / min, and the holding time is 360min. After heat treatment, the bar is cooled to room temperature by oil cooling, and then artificially aged at 720℃ for 6 hours and air cooled to room temperature.

[0073] Example 6 Step 1: Add small-particle 0a grade sponge titanium and aluminum in the form of intermediate alloy and aluminum granules. Add the remaining elements in the form of intermediate alloy. After weighing the ingredients according to the formula of 5.8 wt.% aluminum, 1 wt.% molybdenum, 1 wt.% tungsten, 0.25 wt.% ruthenium, and the balance being titanium, mix them evenly to obtain mixed metal powder.

[0074] Step 2: Press the above uniformly mixed ingredients into electrodes using a hydraulic press. The density of the electrode blocks is 3.4~3.65 g / cm3. Stack and weld multiple electrode blocks into consumable electrodes. Repeatedly melt the alloy raw materials 4 times in a vacuum consumable electrode arc melting furnace at a temperature of

[1880] ~

[1900] ℃ to ensure the uniformity of the ingot composition. After the ingot melting is completed, the riser is removed. Step 3: Using a resistance furnace, heat the corrosion-resistant titanium alloy ingot to 1150℃ in the single-phase region for homogenization treatment. Then, use a high-speed forging machine or hydraulic press to repeatedly upset and draw the ingot three times, with a forging ratio of not less than 2.5 per forging. The initial forging temperature should be ≥1050℃, and the final forging temperature should be ≥940℃. Before forging, chamfer the edges at a speed of 40~60 mm / s (upsetting deformation should be 50%, and the drawing circumference should match the height-to-diameter ratio of 2.5:1). Upset the 690×1320 cm ingot to 590±10 cm, draw it to 620×L cm, and chamfer it to 675±10×1250 cm.

[0075] Step 4: Using a resistance furnace, heat the corrosion-resistant titanium alloy after billet preparation to the α+β two-phase region at a temperature of 1000℃. Then, repeatedly upsetting and drawing the billet three times using a high-speed forging mill or hydraulic press. The forging ratio per forging pass should be no less than 2.8, the total forging ratio no less than 6, and the final forging temperature no less than 850℃. The drawing rate is 20~25mm / s. The billet can be reheated as needed and drawn again. For an octagonal billet of 675×1250cm, draw it to 450±10cm, reheat it in the furnace for 150min, and then draw it to 350×3500cm.

[0076] Step 5: Heat treatment is performed on the hot-forged titanium alloy bar. The heat treatment method is solution treatment, the temperature is 1020℃, the heating rate is 10℃ / min, and the holding time is 360min. After heat treatment, the bar is cooled to room temperature by oil cooling, and then artificially aged at 720℃ for 6 hours and air cooled to room temperature.

[0077] Example 7 Step 1: Add small-particle 0a grade sponge titanium and aluminum in the form of intermediate alloy and aluminum granules. Add the remaining elements in the form of intermediate alloy. After weighing the ingredients according to the formula of 5.8 wt.% aluminum, 1 wt.% molybdenum, 1 wt.% tungsten, 0.25 wt.% ruthenium, and the balance being titanium, mix them evenly to obtain mixed metal powder.

[0078] Step 2: Press the above uniformly mixed ingredients into electrodes using a hydraulic press. The density of the electrode blocks is 3.4~3.65 g / cm3. Stack and weld multiple electrode blocks into consumable electrodes. Repeatedly melt the alloy raw materials 4 times in a vacuum consumable electrode arc melting furnace at a temperature of

[1880] ~

[1900] ℃ to ensure the uniformity of the ingot composition. After the ingot melting is completed, the riser is removed. Step 3: Using a resistance furnace, heat the corrosion-resistant titanium alloy ingot to 1150℃ in the single-phase region for homogenization treatment. Then, use a high-speed forging machine or hydraulic press to repeatedly upset and draw the ingot three times, with a forging ratio of not less than 2.5 per forging. The initial forging temperature should be ≥1050℃, and the final forging temperature should be ≥940℃. Before forging, chamfer the edges at a speed of 40~60 mm / s (upsetting deformation should be 50%, and the drawing circumference should match the height-to-diameter ratio of 2.5:1). Upset the 690×1320 cm ingot to 590±10 cm, draw it to 620×L cm, and chamfer it to 675±10×1250 cm.

[0079] Step 4: Using a resistance furnace, heat the corrosion-resistant titanium alloy after billet preparation to the α+β two-phase region at a temperature of 1000℃. Then, repeatedly upsetting and drawing the billet three times using a high-speed forging mill or hydraulic press. The forging ratio per forging pass should be no less than 2.8, the total forging ratio no less than 6, and the final forging temperature no less than 850℃. The drawing rate is 20~25mm / s. The billet can be reheated as needed and drawn again. For an octagonal billet of 675×1250cm, draw it to 450±10cm, reheat it in the furnace for 150min, and then draw it to 350×3500cm.

[0080] Step 5: Heat treatment is performed on the hot-forged titanium alloy bar. The heat treatment method is solution treatment, the temperature is 1020℃, the heating rate is 10℃ / min, and the holding time is 360min. After heat treatment, the bar is cooled to room temperature by oil cooling, and then artificially aged at 720℃ for 6 hours and air cooled to room temperature.

[0081] Example 8 Step 1: Add small-particle 0a grade sponge titanium and aluminum in the form of intermediate alloy and aluminum granules. Add the remaining elements in the form of intermediate alloy. After weighing the ingredients according to the formula of 5.8 wt.% aluminum, 1 wt.% molybdenum, 1 wt.% tungsten, 0.25 wt.% ruthenium, and the balance being titanium, mix them evenly to obtain mixed metal powder.

[0082] Step 2: Press the above uniformly mixed ingredients into electrodes using a hydraulic press. The density of the electrode blocks is 3.4~3.65 g / cm3. Stack and weld multiple electrode blocks into consumable electrodes. Repeatedly melt the alloy raw materials 4 times in a vacuum consumable electrode arc melting furnace at a temperature of

[1880] ~

[1900] ℃ to ensure the uniformity of the ingot composition. After the ingot melting is completed, the riser is removed. Step 3: Using a resistance furnace, heat the corrosion-resistant titanium alloy ingot to 1150℃ in the single-phase region for homogenization treatment. Then, use a high-speed forging machine or hydraulic press to repeatedly upset and draw the ingot three times, with a forging ratio of not less than 2.5 per forging. The initial forging temperature should be ≥1050℃, and the final forging temperature should be ≥940℃. Before forging, chamfer the edges at a speed of 40~60 mm / s (upsetting deformation should be 50%, and the drawing circumference should match the height-to-diameter ratio of 2.5:1). Upset the 690×1320 cm ingot to 590±10 cm, draw it to 620×L cm, and chamfer it to 675±10×1250 cm.

[0083] Step 4: Using a resistance furnace, heat the corrosion-resistant titanium alloy after billet preparation to the α+β two-phase region at a temperature of 1000℃. Then, repeatedly upsetting and drawing the billet three times using a high-speed forging mill or hydraulic press. The forging ratio per forging pass should be no less than 2.8, the total forging ratio no less than 6, and the final forging temperature no less than 850℃. The drawing rate is 20~25mm / s. The billet can be reheated as needed and drawn again. For an octagonal billet of 675×1250cm, draw it to 450±10cm, reheat it in the furnace for 150min, and then draw it to 350×3500cm.

[0084] Step 5: Heat treatment is performed on the hot-forged titanium alloy bar. The heat treatment method is solution treatment, the temperature is 1020℃, the heating rate is 10℃ / min, and the holding time is 360min. After heat treatment, the bar is cooled to room temperature by oil cooling, and then artificially aged at 720℃ for 6 hours and air cooled to room temperature.

[0085] Figure 3 , 4 Images 5, 6, 7, and 8 are optical microscope metallographic images of the titanium alloys prepared in Examples 3, 4, 5, 6, 7, and 8, respectively. The equiaxed α phase size is approximately 40~80μm. Figure 9 The image shows a high-resolution TEM image of the equiaxed α grain boundary, revealing the Ru atom offsets at the interface.

[0086] Samples meeting corrosion resistance testing requirements were prepared from titanium alloy plates obtained in Example 2 and CP-Ti. Using a Donghua DH7002 electrochemical workstation and a conventional three-electrode system, the electrochemical corrosion behavior of the alloy was tested at room temperature with 3.5 wt% NaCl solution, yielding the following results: Figure 10The potentiodynamic polarization curves under 3.5 wt% NaCl solution conditions are shown. The corrosion potentials and corrosion current densities of Example 2 and CP-Ti can be obtained by extrapolation of the Tafel curves. The corrosion potential Ecorr (V) of Example 2 is -0.59004, while the corrosion current is Icorr (uA·cm2) 0.96. The corrosion potential Ecorr (V) of CP-Ti is -0.28101, while the corrosion current is Icorr (uA·cm2) 1.92. According to the principle of corrosion electrochemistry, the more negative Ecorr is, the greater the corrosion tendency; the more positive Ecorr is, the smaller the corrosion tendency. However, Ecorr only indicates the probability of corrosion. To determine the actual rate of corrosion, the corrosion current Icorr needs to be used. Based on the previous calculations, it is clear that the corrosion density of Example 2 is much smaller than the corrosion current density of CP-Ti. Therefore, Example 2 has stronger corrosion resistance than CP-Ti.

[0087] Example 9 Please see Figure 2 As shown, a method for preparing a corrosion-resistant titanium alloy bar includes the following steps: S1: The raw materials containing titanium, aluminum, molybdenum, zirconium and ruthenium are precisely weighed and mixed evenly in proportion, and pressed into electrode blocks with a certain density; multiple electrode blocks are welded into consumable electrodes; in a vacuum environment, the consumable electrodes are melted multiple times using a consumable electrode arc melting furnace to obtain titanium alloy ingots with uniform composition.

[0088] S2: Heat the titanium alloy ingot obtained in step one to the temperature of the single-phase region of titanium alloy for homogenization and heat preservation treatment; after the heat preservation is completed, use forging equipment at high temperature to repeatedly upset and draw the ingot, and control the deformation amount of each forging and the final temperature of forging.

[0089] S3: Heat the alloy after the forging in step two to the temperature of the two-phase region where the α and β phases of titanium alloy coexist and hold it at that temperature. After holding, use forging equipment again to perform repeated upsetting and drawing forging operations at the temperature of the two-phase region, control the amount of deformation per forging, the total cumulative deformation, and the final temperature of forging, and finally forge into bars of the required specifications.

[0090] S4: Heat the titanium alloy bar obtained by forging in step three to the solution temperature and hold it at that temperature. After holding, cool the bar to room temperature using a rapid cooling method. Then, heat the bar to the aging temperature and hold it at that temperature. After holding, cool the bar to room temperature using an air cooling method. Finally, obtain the corrosion-resistant titanium alloy bar product with the microstructure characteristics described in claim 1.

[0091] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0092] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A corrosion-resistant titanium alloy rod and its preparation method, characterized in that, include: In a first aspect, the present invention provides a corrosion-resistant titanium alloy comprising elements such as aluminum, molybdenum, tungsten, and the noble metal ruthenium; the corrosion-resistant titanium alloy rod, by mass content, contains Al 5.6-6.0, Ru 0.15-0.25, Mo 0.8-1.2, Zr 1.5-2.0, O≤0.12, N≤0.05, with the balance being Ti and unavoidable impurities; it has an equiaxed α-grain structure of 8-15 μm, continuous Ti, Ru, and Mo distribution at grain boundaries, an O2 nanofilm of 2-5 nm, and an Al3Zr precipitate phase less than 200 nm within the grains. Secondly, the present invention provides a method for preparing a corrosion-resistant titanium alloy, comprising the following steps: Step 1: Melt the alloy raw materials to obtain a cast alloy billet; Step 2: The as-cast alloy is subjected to high-temperature billet treatment, followed by hot forging treatment to obtain titanium alloy bars. Step 3: Heat treat the densified alloy rod to obtain the finished corrosion-resistant titanium alloy rod. Raw material smelting and ingot preparation: The raw materials containing titanium, aluminum, molybdenum, zirconium and ruthenium are accurately weighed and mixed evenly in proportion, and pressed into electrode blocks with a certain density; multiple electrode blocks are welded into consumable electrodes; in a vacuum environment, the consumable electrodes are smelted multiple times using a consumable electrode arc melting furnace to obtain titanium alloy ingots with uniform composition. High-temperature forging: The titanium alloy ingot obtained in step one is heated to the temperature of the single-phase region of titanium alloy and then subjected to homogenization and heat preservation treatment. After the heat preservation is completed, the ingot is repeatedly upset and drawn under high temperature using forging equipment to control the deformation amount and the final temperature of each forging. Two-phase region forging: The alloy after the blanking forging in step two is heated to the temperature of the two-phase region where the α phase and β phase of titanium alloy coexist and held at that temperature. After the heat preservation is completed, the forging equipment is used again to perform repeated upsetting and drawing forging operations at the temperature in the two-phase region. The deformation amount of each heat, the cumulative total deformation amount and the final temperature of forging are controlled to finally forge the bar stock of the required specifications. Solution aging heat treatment: The titanium alloy bar obtained by forging in step three is heated to the solution temperature and held at that temperature. After holding, the bar is cooled to room temperature by rapid cooling. Then, the bar is heated to the aging temperature and held at that temperature. After holding, the bar is cooled to room temperature by air cooling. Finally, a corrosion-resistant titanium alloy bar product with the microstructure characteristics described in claim 1 is obtained.

2. The corrosion-resistant titanium alloy rod and its preparation method according to claim 1, characterized in that... Refined control of the smelting process: When using a vacuum consumable electrode arc melting furnace, the melting process needs to be repeated 3-4 times to ensure the uniformity of the alloy composition. If the number of melting times is insufficient, element segregation is likely to occur, reducing the corrosion resistance. The density of the electrode block is strictly controlled within the range of 3.4-3.65 g / cm³; if the density is too low, impurities are more likely to fall off during smelting, increasing the risk of inclusions and damaging the uniformity of the structure. The melting temperature is limited to 1900-1920℃; deviation from the temperature will cause elements such as ruthenium and molybdenum to volatilize or oxidize, weakening the ability to form grain boundary nanofilms.

3. The corrosion-resistant titanium alloy rod and its preparation method according to claim 1, characterized in that... Microstructure control in single-phase forging: The ingot is heated to the single-phase region of 1130-1180℃ for homogenization treatment; if the temperature is below 1130℃, the primary α phase cannot be completely dissolved, leading to the risk of forging cracks; if the temperature is above 1180℃, the grains grow abnormally, weakening the strength. The forging ratio per heat should not be less than 2, and the total forging ratio is achieved through 1-3 heats. Insufficient forging ratio will lead to insufficient crushing of the original β grains. When the final forging temperature is below 940℃, the deformation resistance will surge and microcracks will easily form. The initial forging temperature should be ≥1050℃ to ensure that the material is in the single-phase region; if the temperature is too low, some α phase residue will hinder dynamic recrystallization and make it impossible to obtain equiaxed primary α phase.

4. The corrosion-resistant titanium alloy rod and its preparation method according to claim 1, characterized in that... Phase ratio control in two-phase forging: The forging billet is heated to 980℃ in the α+β two-phase region for secondary forging. Temperature deviation will change the α / β phase ratio. If it is below 980℃, the thickness of the secondary α phase lath increases and the creep performance is reduced. If it is above 980℃, the proportion of equiaxed α phase decreases and the thermal stability is affected. The forging ratio per firing is ≥2.6, and the total forging ratio is ≥8. Insufficient forging ratio will lead to uneven distribution of secondary α phase. When the final forging temperature is below 850℃, the β phase transformation is incomplete, and the residual stress increases. During the elongation process, the height-to-diameter ratio should be controlled at 2:1, and the upsetting deformation should be ≥50%. Imbalance in shape proportions or insufficient deformation will lead to uneven texture and weaken isotropic properties.

5. The corrosion-resistant titanium alloy rod and its preparation method according to claim 1, characterized in that... Optimization of the aging response of solution treatment: Repeated upsetting and drawing deformation can more effectively break up coarse as-cast structures, promote dynamic recrystallization, and achieve full grain refinement and homogenization. The solution treatment temperature should be 1020℃ or 990℃, and the heating rate should be 6-15℃ / min. Temperatures that are too high, above 1020℃, will cause the oxide film at the grain boundaries to crack, and heating rates that are too fast, above 15℃ / min, will cause thermal stress cracking. The holding time should be 150-360 min; if the time is less than 150 min, the solute elements will not diffuse sufficiently, and if the time is too long, the grains will coarsen and the elongation will be reduced. After solution treatment, rapid cooling with oil is used; if air cooling or water cooling is used, mismatched cooling rates will result in residual non-equilibrium structures, affecting the aging response.

6. The corrosion-resistant titanium alloy rod and its preparation method according to claim 1, characterized in that... Phase control during aging treatment: The aging temperature is 650-750℃, and the holding time is 6-8 hours. When the temperature is below 650℃, the nucleation driving force of the precipitated phase is insufficient, and when the temperature is above 750℃, the precipitated phase coarsens, both of which will reduce the strengthening effect. The heat preservation time should be strictly controlled within 6-8 hours; less than 6 hours will result in insufficient density of the precipitated phase, while more than 8 hours will cause over-aging and strength reduction. After aging, air cooling to room temperature should be used; if forced air cooling or water cooling is used, the cooling rate will be too fast, which will lead to residual stress concentration and increase the tendency to crack.

7. The corrosion-resistant titanium alloy rod and its preparation method according to claim 1, characterized in that... Post-forging processing and raw material control: After forging, the bar stock is rolled into a round shape; if this process is omitted, residual surface defects will become corrosion initiation points, shortening the service life. The final forging temperature is controlled at ≥850℃ throughout the process; a lower temperature leads to an imbalance in the retention ratio of the β phase, which destroys the synergistic strengthening effect between the equiaxed α phase and the lath α phase. The raw material is 0A grade sponge titanium with a particle size of 3-12.7mm. If the particle size is too large (greater than 12.7mm), it will introduce shrinkage cavities; if it is too small (less than 3mm), it will be easily oxidized, both of which will deteriorate the corrosion resistance.